Supplementing Ca salts of soybean oil after artificial insemination increases pregnancy success in Bos taurus beef cows. (24th April 2018) - Brandão, Alice P; Cooke, Reinaldo F; Schubach, Kelsey M; Marques, Rodrigo S; Bohnert, David W; Carvalho, Rafael S; Dias, Nicholas W; Timlin, Claire L; Clark-Deener, Sherrie; Currin, John F; Jump, Donald B; Pohler, Ky G; et al.
Abstract: Two experiments investigated the effects of supplementing Ca salts of soybean oil (CSSO) during early gestation on reproductive function and pregnancy rates to AI in Bos taurus beef cows. In Exp. 1, 771 suckled, lactating, multiparous Angus cows were divided into 22 groups of approximately 35 cows per group and timed inseminated on day 0. After AI, groups were assigned randomly to receive (as-fed basis) 100 g of ground corn + 100 g of soybean meal per cow/d, in addition to 1) 100 g/cow daily of CSSO ( n = 11) or 2) 87 g of prilled saturated fat + 13 g of limestone per cow/d (CON; n = 11). Groups were maintained in individual tall fescue-dominated pastures and offered treatments from day 0 to 21. Pregnancy status was determined between days 45 and 55 via transrectal ultrasonography. Cows receiving CSSO had greater ( P = 0.01) pregnancy rates to timed AI compared with CON (60.2 vs. 51.7%; SEM = 4.2). In Exp. 2, 90 suckled, lactating, multiparous Angus × Hereford cows housed in 18 drylot pens (5 cows per pen) were assigned to the same timed AI program and treatments from Exp. 1 (9 pens per treatment) and received 20 kg/d (DM basis) of grass–alfalfa hay. Transrectal ultrasonography was performed to verify ovulation and corpus luteum (CL) volume before AI (day 0), on days 7 and 15. After ultrasonography on day 15, cows diagnosed without a CL on day 0, but with a CL greater than 0.38 cm 3 in volume on days 7 and 15 (2 or 3 cows per pen; CSSO, n = 20; CON, n = 24), were assigned to conceptus collection via transcervical flushing and endometrial biopsy in the uterine horn ipsilateral to the CL. Blood samples were collected for FA analysis on days 0, 7, and 15. Blood was collected from cows not assigned to conceptus collection for whole-blood RNA extraction on day 20 and for pregnancy diagnosis on day 30 by measuring concentrations of pregnancy-associated glycoproteins. Cows receiving CSSO had greater ( P ≤ 0.04) mean plasma concentrations of linoleic acid and ω-6 FA compared with CON on days 7 and 15. Moreover, CSSO supplementation increased ( P = 0.05) mRNA expression of interferon-tau by the conceptus and blood mRNA expression of interferon-stimulated gene 15 and 20, 50-oligoadenylate synthetase on day 20 in gestating cows. Hence, post-AI CSSO supplementation to B. taurus beef cows improved pregnancy rates to timed AI, which can be associated with increased mRNA expression of interferon-tau by the conceptus when CSSO is supplemented during early gestation.